2002
DOI: 10.1002/glia.10124
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces rapid, calcium‐dependent release of vesicular glutamate and ATP from cultured rat astrocytes

Abstract: Nitric oxide (NO; 1 M) or an NO donor (500 M diethylenetriamine-nitric oxide, DETA-NONOate) caused rapid glutamate and ATP release from cultured rat cortical astrocytes. NO-induced glutamate release was prevented by calcium chelators (EGTA or BAPTA-AM) and an inhibitor of vesicular exocytosis (botulinum neurotoxin C, BoTx-C), but not by a glutamate transport inhibitor, L-trans-pyrrolidine-2,4-dicarboxylate (t-PDC), a cyclooxygenase inhibitor (indomethacin), or an inhibitor of soluble guanylate cyclase 1H-[1,2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
136
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 79 publications
5
136
0
2
Order By: Relevance
“…A recent single-vesicle imaging study has provided evidence for astrocyte exocytosis [52]. On the basis of sensitivity to bafilomycin A 1 , tetanus neurotoxin, botulinum neurotoxin C and Ca 2+ chelators, it was suggested that mechanostress-or NO-induced ATP release from rat astrocytes is mediated by exocytosis [23,28]. In the present study, however, intracellular Ca 2+ chelation by pretreatment with a Ca 2+ chelator, BAPTA-AM, and an inhibitor of vesicular transport, BFA, failed to inhibit swelling-induced ATP release from mouse astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent single-vesicle imaging study has provided evidence for astrocyte exocytosis [52]. On the basis of sensitivity to bafilomycin A 1 , tetanus neurotoxin, botulinum neurotoxin C and Ca 2+ chelators, it was suggested that mechanostress-or NO-induced ATP release from rat astrocytes is mediated by exocytosis [23,28]. In the present study, however, intracellular Ca 2+ chelation by pretreatment with a Ca 2+ chelator, BAPTA-AM, and an inhibitor of vesicular transport, BFA, failed to inhibit swelling-induced ATP release from mouse astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes have been shown to release ATP in a non-lytic manner in response to osmotic swelling [11], mechanical stimulation [8,[20][21][22][23], deprivation of extracellular Ca 2+ [22][23][24], and stimulation with glutamate [7], UTP [25,26], noradrenaline [27] or NO [28]. However, the precise pathway for ATP release remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytic release of glutamate (Bezzi et al, 1998;Parpura et al, 1994;Pasti et al, 2001), ATP (Bal-Price et al, 2002;Coco et al, 2003), of the secretory granule protein secretogranin II (Calegari et al, 1999), and of atrial natriuretic peptide (Krzan et al, 2003) were found to depend on an increase in intracellular Ca 2+ concentrations. Furthermore, prolonged incubation of astrocytes with the botulinum neurotoxins A, C 1 and B, or with tetanus toxin (which cleave the SNARE proteins SNAP-25, syntaxin I, and synaptobrevin II/cellubrevin, respectively) resulted in attenuated receptor-evoked glutamate release (Araque et al, 2000;Jeftinija et al, 1997;Pasti et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…In particular, ATP is released from erythrocytes, which, under physiological conditions, are vesicle-free (7). Various channels have been implicated in the process, including CFTR (cystic fibrosis transmembrane conductance regulator), connexin 43 (Cx43) hemichannels, a volumeregulated channel (VRAC), and the purinergic receptor P2X7 (5,6,(8)(9)(10)(11). However, the evidence for their involvement falls short because of questionable specificity of the pharmacological blockers used to determine channel identity.…”
mentioning
confidence: 99%
“…Two general release modes have been proposed: (i) vesicular release akin to the exocytotic release of transmitters and (ii) channel-mediated release. Although vesicular ATP release is well documented (5,6), it cannot account for all of the ATP release phenomena. In particular, ATP is released from erythrocytes, which, under physiological conditions, are vesicle-free (7).…”
mentioning
confidence: 99%